Map of a portion of the Arctic shores of America to accompany Captn. Mc Clintock's narrative / compiled by John Arrowsmith - Arrowsmith, John, 1790-1873 (John Murray; Thos. S. Wagner's Lith., 1859)
Contained in (work): M'Clintock, Francis Leopold, Sir, 1819-1907. Voyage of the "Fox" in the Arctic seas Notes Relief shown by spot heights.; Includes inset of the Bellot Strait.; Issued as accompanying material to: The voyage of the "Fox" in the Arctic seas : a narrative of the discovery of the fate of Sir John Franklin and his companions / by Captain M'Clintock.; "Sketch map of Arctic regions at the time of Franklin's last expediton" and printed ship's log cover form (in multiple languages) on verso. Color; 1:50,688